Usaha Pembesaran dan Pemasaran Ikan Lele serta Strategi Pengembanganya di UD Sumber Rezeki Parung, Jawa Barat - - Jaja; Ani Suryani; Komar Sumantadinata (Institut Pertanian Bogor, 2013)
The purpose of this study was to determine the magnification and technology marketing at UD Sumber Rezeki and get a new breakthrough in marketing efforts and the enlargement of catfish, determine the feasibility and efficiency of marketing efforts and the enlargement of catfish, find the prospect of catfish processed products, know the SWOT in the enlargement and marketing of catfish and determine the strategy of business development and marketing of catfish enlargement on UD Sumber Rezeki. Technology production processes carried out by following the catfish aquaculture activities at UD Sumber Rezeki Parung, West Java, and then analyzed the feasibility of their business. The analisis through qualitative analysis, quantitative analysis of IFE and EFE, Matrix IE and SWOT. Catfish farming in the UD Sumber Rezeki Parung, West Java feasible to be implemented with the value of B/C ratio > 1,26. BEP catfish production. Rp9631.76 per kg, NPV 14% on the value of Rp38,140,956, 17% IRR and PBP 3 years 9 months. Efficiency for catfish enlargement in UD Sumber Rezeki determined by the use of water by gravity, the use of probiotics to save time, use sinking feed and floating feed. Based on the IFE (2.83) and EFE (2.81), then the position at UD Sumber Rezeki phase of growth and stability and are in quadrant 5. Based on the analysis of SWOT matrix and IE matrix, then the strategy for developing UD Sumber Rezeki, Parung, West Java are (1) market penetration by selling directly to end customer, (2) diversification of catfish products and (3) improve the competence of human resources.